Congélation en présence de micro-ondes : application à la viande de porc - Xanthakis, Epameinondas; LeBail, Alain; Ramaswamy, Hosahalli Swamy (My University, 2014)
A new concept based on the application of microwave irradiation during freezing of a food matrix has been investigated. The process was applied to pork tenderloin samples using a prototype system. The application of microwaves was performed at selected time intervals, resulting in temperature oscillations during freezing. A 62% reduction in the size of ice crystals and a decrease in the degree of supercooling of around 92% has been observed in the presence of microwaves compared to the conventional freezing process. These results showed that the application of microwave irradiation during freezing may diminish freeze damage of tissues such as meat. This article is based on a more comprehensive paper published recently [ref. 9].
Keywords: Technology; Ice; Microwave; Pork; Crystallization; Freezing